Impact of drying techniques on volatile aroma profiles and formation mechanisms of black soybean thua nao - Pakavit Mathatheeranan; Ting-Jang Lu; Thanakorn Wongprasert; Yi-Ci Jhu; Hsin-Jo Chang; Wei-Yuan Wu; Mingchih Fang; Kitipong Assatarakul; Inthawoot Suppavorasatit (Food Chemistry: X)
Thua nao, a traditional Thai fermented soybean, offers a unique aroma and nutritional value. However, fresh thua nao cannot be stored for long periods due to its high in water activity (aw). This study examined the effects of various drying methods, including natural sun drying and machine drying methods, namely hot air, microwave vacuum (MIC), and vacuum drying on the qualities of dried black soybean thua nao. Our findings showed that MIC-treated sample showed the lowest aw and highest crude fat and TVB-N contents. Volatile aroma compounds were categorized according to odor description and clustered using principal component analysis (PCA). Drying methods influenced volatile compounds associated with lipid oxidation (green-fatty attribute) and the Maillard reaction (nutty-roasted, sweet, sulfurous, and smoky attributes). PCA results indicated that volatile profiles of the sun-dried sample differed from the others. This research establishes a correlation between sugar and free fatty acid precursors and aroma attributes.